Dental health for children with special educational needs and disability. Issue 8 (August 2022) - Carter, Annabelle; Clarke, Lisa; Stevens, Claire
Abstract: There are 1.37 million children and young people (CYP) with special educational needs and disability (SEND) in the UK. These CYP have more complex needs and may require more expertise, support and reasonable adjustments in the dental setting. There are high levels of unmet dental need for this cohort of CYP. Unmanaged dental disease, such as dental caries, can impact on a child's quality of life and wellbeing. All healthcare professionals who have contact with CYP with SEND have an important role to play in trying to improve the oral health of their patients. This can be achieved by educating parents, carers and patients, delivering consistent and supportive dental preventative messages, and where required, liaising with, or signposting to dental professionals. This paper outlines oral conditions that CYP with SEND experience, how they are managed by the dental team, reasonable adjustments, and evidence-based guidelines that should be followed to help prevent and treat oral disease.